Real-time optimized wireless networked control system with cooperative network protocols - Yousif Safaa Alobaidy; Osama Ali Awad (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
In this paper, we present a real-time optimized fuzzy fuzzy proportional integral derivative (FPID)-controlled wireless networked system for a high-torque direct current (DC) motor. The main challenge faced by such systems is the delay in the wireless networked control system (WNCS). We employed a powerful FPID controller tuned using particle swarm optimization (PSO) technique to compensate for the delay. The system is tested on a network using the TrueTime simulator with different parameters. The results show that the system exhibits a very stable response, with the FPID controller compensating for the delay effectively. Increasing the number of nodes negatively impacts the system's performance, resulting in higher overshoot, longer settling time, and longer rise time. Moreover, the choice of bandwidth share and sampling time significantly affects the system's stability and real-time response. The use of transmission control protocol/internet protocol (TCP/IP) or user datagram protocol (UDP) protocols with Node MCU is necessary to transfer data from the Arduino Microcontroller to MATLAB, as MATLAB TrueTime simulator does not support direct serial communication. In conclusion, this study highlights valuable insights into the performance of the proposed system, demonstrating the need for further improvements in the system's design and control algorithms to achieve stable operation.